English Language Teachers’ Classroom Practices in Ibadan, Nigeria - Olaosebikan, Bolape Olufunto; Kolawole, C.O.O. (International Journal of Social Learning (IJSL), 2023)
The focus of the research is to find out about the practice of English teachers in the classroom because teachers are the best model for students' acquisition of linguistic knowledge and what they do in class during the teaching and learning process. Although all English teachers are responsible for transferring linguistic expertise to students in class, their classroom practices differ. Therefore, this study qualitatively examines the classroom practice of English teachers in the Akinyele Local Government, Ibadan, Nigeria. This study adopted a mixed methods research design. The findings reveal that English teachers in Akinyele Municipality, Ibadan, Nigeria, use a traditional approach to teach students, paper and pencil tests primarily to assess students, engage in learning assessment and enforce classroom rules to manage their classrooms. Based on the findings, it is recommended that English teachers improve their classroom practices and update their teaching methods with modern ones.